Intercultural Communicative Competence in the Polish educational context: EFL primary school teachers’ practices and opinions - Cholewa, Wiktoria (Glottodidactica, 2024)
Intercultural Communicative Competence (ICC) is defined as“a complex of abilities (including host language proficiency) that are needed to perform effectively and appropriately when interacting with others who are linguistically and culturally different from oneself”(Fantini 2020: 5). The development of ICC in learners has been recognised as one of the key elements of foreign language (L2) education by, for instance, the Council of Europe (2022). The article presents the findings of a study conducted among primary school teachers of English which investigated their practices in teaching and assessing ICC, as well as their opinions on coursebook content and on learner motivation regarding ICC development. Quantitative and qualitative data have been gathered by means of a questionnaire administered to 39 teachers of English and interviews conducted with five teachers of English. The findings show that most respondents attempt to prioritise integrating ICC into English courses and aim to develop students’ICC. However, less than half give ICC equal importance to language in their teaching. Moreover, most participants often rely on teaching national attributes to foster ICC.